ANALISIS FAKTOR YANG MEMPENGARUHI PARTISIPASI DAN NILAI PENAWARAN PESERTA LELANG ELEKTRONIK (E-PROCUREMENT) JASA KONSTRUKSI DI KABUPATEN BULELENG - Respawan, Made; Sudarsana, I K; Nadiasa, Mayun (JURNAL SPEKTRAN; Vol 5 No 1 (2017): Vol. 5, No. 1, Januari 2017DO - 10.24843/SPEKTRAN.2017.v05.i01.p01, 2017)
Abstract : Starting in 2012 the procurement of government goods/services in Buleleng done electronically (E -Procurement) to the procedure E -Tendering. In the implementation of participation and the bid price tends to decrease the auction participants both during the auction at the current conventional and electronic auctions. This study aims to determine the factors that influence participation and value of the electronic auction participants offer construction services in Buleleng, and what factors influence most dominant. The sample used in this study as many as 53 companies contracting in Buleleng that the sample collection was done by using a non probability sampling with purposive sampling and data collection using questionnaires and interviews. Data was analyzed using factor analysis. The factor analysis forms 11 new factors that influence the participation of bidders with cumulative variance 79,198%, which is made up of 42 variables. The most dominant factors, indicated by eigenvalues of 20.738 and variance of 42.323% is formed by 11 variables, namely, project location, great value for the project, environmental security project, started the project approaching the end of the year, without face-to-face opportunities to minimize collusion, corruption and nepotism, term timing of the access road to the project site, implementation of the rainy season, the terms of ISO certificate, the terms of financial support of banks and variable auctioneer. While the analysis of the factors affecting the bid price auction participants generate 10 new factors with cumulative variance 78,925%, which is made up of 43 variables. The most dominant factors indicated by eigenvalues of 22.756 and  variance of 47.409% is formed by nine variables, namely, fluctuations in material prices, the return on investment, fluctuations in foreign exchange rates (dollars), the access road to the project site, the opportunity to gain a larger project, the risks of investing, the rate of inflation, more cost-effective without document printing costs and transportation costs and the ability to offer estimates.
Keywords: Participation, Value offer, E-Procurement, Construction work.